Sistem Electronic Supply Chain Management Menggunakan Metode Just in Time di PT Cemara Agung Mandiri - Rafii Muhammad Afif; Eddie Krishna Putra; Tacbir Hendro Pudjiantoro (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
In the process of developing supply chain management, it is very important for a company that produces it, so that the production can reach the end users. In meeting the demands of consumers, especially companies engaged in textiles, PT. Cemara Agung Mandiri collaborates with raw material suppliers in order to produce equipment that meets customer needs. PT. Cemara Agung Mandiri is a company engaged in the weaving and textile industry with raw materials in the form of threads through machining fabrication to produce the required fabric, but when checking the raw materials at ADM warehouse, there are often irregular in and out of goods then with irregular in and out. Raw materials often occur delays in ordering goods with suppliers, resulting in delays in the production process. The method to be used is to use the Just In Time method, which is a method that has a method of production that determines the amount based only on the number of goods that will actually be sold, needed, produced in each part exactly as needed. In order for coordination and cooperation in the company's supply chain to run smoothly, this research builds Electronic Supply Chain Management software using the just in time method at PT. Cemara Agung Mandiri.